Design and Development of Wide Beamwidth Antenna for Ionosphere Wireless Remote Sensing Applications - Rao, M. D.; Rao, Inabathini Srinivasa (International Journal of Sensors Wireless Communications and Control, 2021)
Background: The Yagi-Uda antenna is a highly directive antenna used widely in many applications including pulsed Doppler radars to study the dynamics of the atmosphere. Yagi antennas configured in planar array configurations in phased array radars to achieve high peak powers to probe the atmosphere from troposphere. In this paper, a two-element Yagi-Uda antenna design is presented to investigate the ionospheric irregularities from the Gadanki Ionospheric Radar Interferometer. A new approach devised for the first time to design the two element, wide beam width tilted Yagi antenna, where folded dipole acts as active driver element and reflector as parasitic element. Methods: Several design techniques have been studied and new approach has been employed in designing the antenna and simulations have been carriedout and optimized the performance at 30 MHz with 14o tilt towards geometric north from vertical (zenith) direction for the maximum back scattered echo gain. Based on the design antenna has been fabricated and the system performance has been evaluated. Detailed validation methods have been listed to validate the parameters like reflection coefficient, gain, bandwidth and front-to-back ratio. Results: The antenna is designed and simulated results with 4NEC2 provided the optimized parameters before fabrication. The measured results indicate that the antenna has a gain of 5.65dBi and a reflection coefficient of -30 dB and these results are in close agreement with the simulation results. The band width obtained is about 2MHz is very good for the ionospheric remote sensing applications. The peak power handling capability upto 1kW shows the reliable system design for continuous and long term use of the system. Conclusion: Two element wide beam width 14o tilted Yagi-Uda antenna at 30MHz has been designed, simulated and optimized. Realized system performance validated to use for ionospheric radar remote sensing application. Details of the test methodologies are explained and the same have been executed to characterize the performance of the fabricated antenna with simulation results by measuring reflection coefficient, gain, radiation pattern. All the measured results have very close agreement with the simulation results and satisfy the design requirements to fit into 30 MHz radar antenna array for dedicated ionospheric probing. In future, we intended to carry out the radiation pattern simulation of the 20x8 phased array antennas to describe the overall radiation pattern.
Keywords: radar communication